An Insilico Study of Isobutrin and Phosphorylase Kinase - A Ray of Hope for Psoriasis Patients – Clinical Hypothesis - Rakshana Manikandan; M. Mala; G. Manikandan; Prakash Vaithyanathan (International Journal of Cheminformatics, 2024)
Psoriasis is a chronic, hyper-proliferative and inflammatory skin disease. Increased levels of the calmodulin-containing enzyme, namely, phosphorylase kinase (PhK), were observed in the human epidermis of the active psoriasis cases. Thus PhK is a potential biomarker for the diagnosis and progression of the skin disease, namely, psoriasis. The search for the potential molecules that could supress the over expression of PhK is underway and any break-through in this direction leads to the alleviation of the suffering of the patients infected with Psoriasis. Fundamental studies revealed curcumin to be a potential inhibitor of PhK. In our study we report that the water soluble edible molecule from the flower petals of Butea monosperma namely, isobutrin, outperforms curcumin, in terms of the intensity of molecular level interactions of isobutrin with the amino acids related to PhK. Molecular docking studies revelated stonger interactions of isobutrin with amino acids characteristics of PhK and the interactions are much stronger than those exhbited with curcumin with similar amino acids of PhK. Thus the therapeutic potential of isobutrin is hypothesised. The results need to be further strengthened by the animal model studies that are underway.
Keywords: Psoriasis; curcumin; isobutrin; molecular docking; phosphorylase kinase